Tassement et consolidation au dégel d'un silt argileux à Kangiqsualujjuaq - Leroueil, Serge; Dionne, Guy; Allard, Michel (Canadian Geotechnical Journal, 1991)
The physical characteristics, the compressibility, and the consolidation of a permafrost clayey silt of Kangiqsualujjuaq, Quebec, have been studied, in the laboratory and in the field, by melting the permafrost in the foundation of an excavation. It appears that the values of the thawing settlement parameter (A 0 ) obtained in the laboratory and in the field coincide perfectly with one another, and with those found in the literature for the same type of soil. It has also been observed, on that site, that the thawing of the permafrost, even though ice-rich, does not generate excess pore pressures. Key words: permafrost, compressibility, consolidation, laboratory, in situ. [Journal translation]